The Diagnostic Yield of Dental Radiography and Cone-Beam Computed Tomography for the Identification of Dentoalveolar Lesions in Cats - Heney, Colleen M.; Arzi, Boaz; Kass, Philip H.; Hatcher, David C.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2019)
The objective of this study was to evaluate the diagnostic yield of dental radiography (DR) and 3 cone-beam computed tomography (CBCT) software modules for the identification of 32 pre-defined dentoalveolar lesions in cats. For 5 feline cadaver heads and 22 client-owned cats admitted for evaluation and treatment of dental disease, 32 predefined dentoalveolar lesions were evaluated separately and scored by use of dental radiography and 3 CBCT software modules [multiplanar reconstructions (MPR), tridimensional (3-D) rendering, and reconstructed panoramic views]. A qualitative scoring system was used. Dentoalveolar lesions were grouped into 14 categories for statistical analysis. Point of reference for presence or absence of a dentoalveolar lesion was determined as the method that could be used to clearly identify the disorder as being present. Accuracy, sensitivity, specificity, and positive and negative predictive values were calculated with the McNemar χ2 test of marginal homogeneity of paired data. When all 3 CBCT software modules were used in combination, the diagnostic yield of CBCT was significantly higher than that of dental radiography for 4 of 14 categories (missing teeth, horizontal bone loss, loss of tooth integrity, feline resorptive lesions), and higher, although not significantly so, for 9 categories (supernumerary teeth, supernumerary roots, abnormally shaped roots, vertical bone loss, buccal bone expansion, periapical disease, inflammatory root resorption, and external replacement root resorption). In conclusion, we found that CBCT provided more clinically relevant detailed information as compared to dental radiography. Therefore, CBCT should be considered better suited for use in diagnosing dentoalveolar lesions in cats.